Highways and heartaches : how Ricky Skaggs, Marty Stuart, and children of the New South saved the soul of country music - Streissguth, Michael (Hachette Books, 2023)
"In a dim clearing off a county road in Kentucky sits a sagging outdoor stage buried in moss and dead leaves. It used to be the centerpiece of carnival-like Sunday afternoons where local guitarists, fiddlers and mandolin players hammered out old mountain ballads while legends from the dawn of country music performed their classic hits. Most of the musicians who showed up have long since passed, but Nashville stars Ricky Skaggs and Marty Stuart survive. They were barely teenagers in the early 1970s when they visited this stage in the care of legends Ralph Stanley and Lester Flatt, respectively. Skaggs and Stuart followed their bosses to dozens of stages throughout Appalachia and deeper into the American southland. They were the children, absorbing the strange and wondrous dramas around them so they might one day bear witness to the scenes along the country music road. Highways and Heartaches takes readers on the rural circuit Skaggs and Stuart traveled, where an acoustic sound rooted in American musical tradition thrived, setting the stage for the wildly popular new traditionalist movement that defined country music in the 1980s before morphing into the Americana phenomenon that has kept country music's soul alive into present times. Through the eyes of Skaggs and Stuart, the book documents the New South which was in the throes of a glaring duality: stealing back jobs, population and cultural influence from the north while continuing to grapple with poverty, isolation and the environmental and human fallout of coal mining, particularly in Appalachia. On the road, Skaggs and Stuart witnessed labor strikes, new suburban housing tracts, aimless Vietnam veterans, creeping drug culture, politicians from a Robert Penn Warren novel, workers in North Carolina flush with cash from jobs in the state's Research Triangle. Still wrestling with the legacy of the Civil War, the region had nonetheless come into the light: courted by Richard Nixon, home to a manufacturing boom, lifting up Jimmy Carter, and exporting music and literature to the world. Nobody ever again ignored the South as current national politics and the sweeping popularity of modern country music can attest. Skaggs and Stuart were also forced to negotiate the hard truths of their performance circuit, brushing up against scheming promoters, unscrupulous record producers, backwoods prostitutes, moonshiners, and preachers warning them away from their chosen careers in music. They wrestled with the road's temptations and tolerated stuffy buses, greasy diners, and clawing fans. Such were the necessary costs of carrying the soul of country music into the 1980s. In Highways and Heartaches, the stories Skaggs and Stuart chronicle an endless Southern drama whose homespun music, undiluted characters, and gyrating socio-economic conditions echo along county roads and help define who we are as a nation. Riveting portraits of shadowy figures emerge for the first time anywhere next to scenes involving legends such as Johnny Cash, Linda Ronstadt, Emmylou Harris, Ralph Stanley, Lester Flatt and Keith Whitley, the troubled bass-baritone singer who ran with Skaggs and Stuart and began his deadly descent into alcoholism in the late 1970s. Together, the known and unknown formed a rich vein of country music that ran from obscure places in the South to the glorious, tradition-fueled, commercial heights of the 1980s"--